Desenvolvimento do raciocínio lógico e educação: um estudo com crianças de quatro a seis anos - Tineli, Cilene (2006)
The theory, which the present study is, based broaches the logical thought as one of the most important process that occurs in the conscience formation. The school is seen as one of the main means of culture transmission historically built by humanity. The study analyses the way of the logical reasoning is reported in 42 children from middle and middle-high income, with ages between four, five and six years old that used to go to a pre school with a quality pedagogical project. By instrument were used syllogistics tests of individual application. The answers were noted down. Points were given to them and the justifies for the answers considered corrects were quality analyses. The results show increase of rights and teorical justifies frequency following the ages and the consequent school series progression of the child. The schooldays are seen with an important place for the logical forms of thought development that hardly would happen without the school culture